Abdimas KKNT Desa Grujugan Pelaksanaan Pendidikan Program Bimbingan Belajar Siswa Sekolah Dasar - Agustin, Cindy Erra; Setyawan, Agung; Citrawati, Tyasmiarni; Mu'ammar (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
This research aims to determine the implementation of the learning guidance program at the KKNT elementary school in Grujugan village. The method used in this research is descriptive qualitative and the data collection techniques used are interviews and observation. The resource person interviewed was a tutoring student from Grujukan village. The results of this research show that tutoring activities really help students in the learning process which is carried out outside class hours at school, they are helped and encouraged to take part in tutoring and easily understand material such as calculating and memorizing English vocabulary. And with the study guidance program held by KKNT UTM, students can improve their ability to solve problems or questions.